2013
DOI: 10.1017/jie.2013.10
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Potential Use of the Collaborative-Geomatics Informatics Tool to Foster Intergenerational Transfer of Knowledge in a Remote First Nation Community

Abstract: Northern First Nations in Canada have experienced environmental change throughout history, adapting to these changes based on personal experience interacting with their environment. Community members of Fort Albany First Nation of northern Ontario, Canada, have voiced their concern that their youths’ connection to the land is diminishing, making this generation more vulnerable to environmental change. Community members previously identified the collaborative-geomatics informatics tool as potentially useful for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Although youth benefited by gaining experience of being on-the-land in the present harvest program, older harvesters identified the need to provide more on-the-land opportunities, so that additional teenagers and youth can gain on-the-land knowledge and skills through experiential learning. Experiential learning is foundational for Indigenous learning [82], and well received by Cree youth [32,83]. Vertical transmission of knowledge was not only between Elders and youth, but also between Elders and adults (e.g., the Elders offered an explanation as to why the snow goose harvest was relatively unsuccessful in 2012; Table 1).…”
Section: Transmission Of Indigenous Knowledge and The Strengthening O...mentioning
confidence: 99%
“…Although youth benefited by gaining experience of being on-the-land in the present harvest program, older harvesters identified the need to provide more on-the-land opportunities, so that additional teenagers and youth can gain on-the-land knowledge and skills through experiential learning. Experiential learning is foundational for Indigenous learning [82], and well received by Cree youth [32,83]. Vertical transmission of knowledge was not only between Elders and youth, but also between Elders and adults (e.g., the Elders offered an explanation as to why the snow goose harvest was relatively unsuccessful in 2012; Table 1).…”
Section: Transmission Of Indigenous Knowledge and The Strengthening O...mentioning
confidence: 99%
“…Concerned about highly pathogenic avian influenza, Indigenous subsistence hunters from a remote northern Canadian community were worried about potential exposures as it is related to food security. 44,45 We combined modern geomatics with IK to better understand bird migratory patterns 46 and assess exposures. 44,45 This partnership included elders and ultimately gave impetus to develop a science outreach camp for youth.…”
Section: Two-eyed Seeing Implementationmentioning
confidence: 99%
“…In the face of the global environmental issues that are hallmarks of the Anthropocene, such as climate change and alarming losses of biodiversity, approaches to management that include intergenerational participation and adaptive learning will be essential [32][33][34]. For example, Isogai et al identified the disruption of intergenerational knowledge transfer as a source of vulnerability in the face of a changing climate, and stated that "the loss of knowledge, coupled with an accelerated rate of environmental change, has made it challenging for northern Indigenous communities to adapt, and has the added potential to increase Indigenous youths' vulnerability to climate change impacts" [33] (p. 45). Such challenges indicate the clear need to build support for environmental governance systems to adapt, such as frameworks that demonstrate pathways for intergenerational collaboration, dialogue, and learning.…”
Section: Framing Intergenerational Collaboration: Dialogue Learningmentioning
confidence: 99%
“…The Buddy Experiment and the iAct Dialogues for Sustainability are two key examples and road maps for other mechanisms which, if supported financially and otherwise, will enhance intergenerational collaboration across all programmatic areas of the IUCN. Such mechanisms connect generations through iterative processes that provide foundations adaptive governance, which is essential for multi-lateral organizations like the IUCN that are tasked with responding to and developing solutions at times of global environmental crisis [4,33]. 4.…”
mentioning
confidence: 99%